Strength deficit in elite young rugby players: differences between playing positions and associations with sprint and jump performance - Zabaloy, S.; Giráldez, J.; Fink, B.; Alcaraz, P. E.; Pereira, L. A.; Freitas, T. T.; Loturco, I. (The Journal of Strength and Conditioning Research, 2022)
The aims of this study were twofold: to compare the strength-related performance between young forwards and backs rugby players and to examine the correlations between strength deficit (SDef), strength parameters, and sprint and jump performance. Fifty-seven male rugby players (mean ± SD: age, 17.4 ± 1.3 years) performed anthropometric and body composition assessments, vertical jumps, 30-m sprint, and squat (SQ) and bench press (BP) 1-repetition maximum tests (1RM SQ and BP). The differences in the tested variables between positions were analyzed through an independent t-test. A Pearson`s correlation coefficient was used to assess the relationships among the variables. Significant differences were observed for anthropometric and body composition measures and jump and sprint performance between positions (p < 0.05; effect size [ES]: 0.60-1.34), except for 5-m velocity (p = 0.080; ES: 0.57). Backs demonstrated higher relative 1RM than forwards in both exercises (p = 0.009 and p = 0.008; ES = 0.88 and 0.91, for SQ and BP, respectively). In addition, backs demonstrated lower SDef from 70 to 90% 1RM (p < 0.048) but small-to-moderate nonsignificant lower SDef against lighter loads compared with forwards (50-60% 1RM). Overall, SDef across all loads (r: -0.378 to -0.529) and 1RM SQ (r: 0.504 to -0.590) were significantly related to sprint performance. Therefore, young rugby players who present lower magnitudes of SDef and superior 1RM SQ performance tend to be faster in linear sprints.